Eicosapentaenoic Acid Enhances the Effects of Mesenchymal Stromal Cell Therapy in Experimental Allergic Asthma - Abreu, Soraia Carvalho; Lopes-Pacheco, Miquéias; da Silva, Adriana Lopes; Xisto, Debora Gonçalves; de Oliveira, Tainá Batista; Kitoko, Jamil Zola; de Castro, Lígia Lins; Amorim, Natália Recardo; Martins, Vanessa; Silva, Luisa H. A.; Gonçalves-de-Albuquerque, Cassiano Felippe; Castro Faria-Neto, Hugo Caire de; et al. (Frontiers in Immunology, 2018)
Asthma is characterized by chronic lung inflammation and airway hyperresponsiveness. Despite recent advances in the understanding of its pathophysiology, asthma remains a major public health problem and, at present, there are no effective interventions capable of reversing airway remodeling. Mesenchymal stromal cell (MSC)-based therapy mitigates lung inflammation in experimental allergic asthma; however, its ability to reduce airway remodeling is limited. We aimed to investigate whether pre-treatment with eicosapentaenoic acid (EPA) potentiates the therapeutic properties of MSCs in experimental allergic asthma. Seventy-two C57BL/6 mice were used. House dust mite (HDM) extract was intranasally administered to induce severe allergic asthma in mice. Unstimulated or EPA-stimulated MSCs were administered intratracheally 24h after final HDM challenge. Lung mechanics, histology, protein levels of biomarkers, and cellularity in bronchoalveolar lavage fluid (BALF), thymus, lymph nodes, and bone marrow were analyzed. Furthermore, the effects of EPA on lipid body formation and secretion of resolvin-D1 (RvD1), prostaglandin E2 (PGE2), interleukin (IL)-10, and transforming growth factor (TGF)-β1 by MSCs were evaluated in vitro. EPA-stimulated MSCs, compared to unstimulated MSCs, yielded greater therapeutic effects by further reducing bronchoconstriction, alveolar collapse, total cell counts (in BALF, bone marrow, and lymph nodes), and collagen fiber content in airways, while increasing IL-10 levels in BALF and M2 macrophage counts in lungs. In conclusion, EPA potentiated MSC-based therapy in experimental allergic asthma, leading to increased secretion of pro-resolution and anti-inflammatory mediators (RvD1, PGE2, IL-10, and TGF-β), modulation of macrophages toward an anti-inflammatory phenotype, and reduction in the remodeling process. Taken together, these modifications may explain the greater improvement in lung mechanics obtained. This may be a promising novel strategy to potentiate MSCs effects.